Rancang Bangun Aplikasi Pencarian Toko Oleh-Oleh Terdekat Berbasis Android Menggunakan Algoritma Floyd Warshall - Mahmud, Mohamad An Nafli; Maryam Hasan; Warid Yunus; Syarifah Fitrah Ramadani (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2024)
Abstract- Information technology develops rapidly. The effect can be seen through the increasing use of mobile devices in supporting daily activities in carrying out various activities. With the development of mobile technology, mobile devices offer a variety of advanced computing capabilities known as smartphones. The role of smartphones is to have a good impact if the embedded applications are equipped with good service quality to support users to do or to search for a place or location. Through supporting applications, users can use it more easily, more economically, and more efficiently. In addition, users can also find out the current developing technology model. The development of souvenir centers depends on tourism industry products regarding the tourism concept and convenience in tourism visits. The tourism sector is also very influential in the socio-cultural field, and of course, in the economic field because it can open up new business opportunities. The design of the nearest souvenir shop search application helps in finding the closest route to the souvenir shop by applying the Floyd Warshall algorithm. The research results produce a system that can find the nearest souvenir shop and is expected to help the community in finding the nearest souvenir shop in Gorontalo City. Keywords: nearest location point search application, souvenir shop, Floyd Warshall algorithm